Asthma and COVID-19: A Comprehensive Review of Clinical Outcomes, Mechanisms and Management Strategies - Piątek, Maja; Jastrzębski, Michał; Hejnosz, Aleksandra; Szczerba, Mateusz; Knysak, Karol; Maj, Alicja Zofia; Wilkowska, Krystyna; Kaczorowski, Wojciech; Michałowski, Maciej Karol; Sudomir, Maria (Quality in Sport, 2025)
The COVID-19 pandemic has posed several significant challenges for individuals with chronic respiratory diseases, particularly asthma. Early concerns suggested that asthma might increase susceptibility to severe COVID-19 complications. Key findings suggest that asthma, especially allergic phenotypes, does not consistently increase the risk of severe COVID-19– in some cases, type 2 inflammation may even be protective. Significant gaps remain in understanding the long-term impacts of COVID-19 on asthma control, and yet this review provides a comprehensive overview of current evidence, identifies knowledge gaps, and offers recommendations for future research and clinical practice.